The association between cannabis abuse and dependence and childhood physical and sexual abuse: Evidence from an offspring of twins design: Cannabis use disorder and child abuse - Duncan, Alexis E. (2008)
AIMS: This study examines the association between childhood physical abuse (CPA) and sexual abuse (CSA) and the development of cannabis abuse and dependence among adolescents and young adults while controlling for genetic and environmental risk factors. DESIGN: To control for familial risk differences related to paternal drug dependence that might confound the relationship between CSA and CPA and cannabis abuse/dependence, we created four groups based on father’s and uncle’s substance use dependence (SUD) status reflecting different degrees of genetic and environmental risks to offspring: 1) high genetic, high environmental risk; 2) high genetic, low environmental risk, 3) medium genetic, low environmental risk; and 4) low genetic, low environmental risk. PARTICIPANTS: Adolescent and young adult offspring of monozygotic and dizygotic US military veteran twin fathers (n= 819). MEASUREMENTS: Data on CPA and CSA, DSM-IV offspring cannabis abuse/dependence, other SUD and psychopathology, and maternal and paternal SUD and psychopathology were collected via semi-structured telephone interview. FINDINGS: Twenty-three percent of the offspring sample met lifetime criteria for cannabis abuse/dependence, 8.55% and 12.82% reported CSA and CPA, respectively. Offspring exposed to CSA, but not CPA, were at significantly greater risk of developing cannabis abuse/dependence compared to those who had not experienced CSA (HR=2.16; 95% CI=1.48–3.16) after controlling for genetic and familial environmental risk and offspring gender, alcohol abuse and dependence and conduct disorder. CONCLUSIONS: These results indicate that there are effects of CSA on development of cannabis abuse/dependence in addition to the genetic and familial environmental risk imparted by having a drug dependent father.